1982
DOI: 10.1161/01.cir.66.6.1277
|View full text |Cite
|
Sign up to set email alerts
|

Digoxin-quinidine interaction in patients with chronic renal failure.

Abstract: SUMMARY We evaluated the effect of quinidine on digoxin pharmacokinetics in six patients with severe renal failure. Quinidine reduced the total body clearance of digoxin from 1.87 to 1.06 1/hour (p < 0.001), and prolonged the digoxin half-life of elimination from 5.20 to 9.61 days (p < 0.01). The digoxin volume of distribution was unchanged. Renal clearance of digoxin was negligible; thus, the decrease in total body clearance was due to a decrease in the nonrenal clearance of digoxin. The mean trough serum con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 13 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…In these patients, dose adjustment is often overlooked for drugs that are predominantly cleared by metabolism and/or transport. However, non-renal clearance of compounds requiring hepatic metabolic clearance is also known to be reduced in ESRD patients [1,2]. …”
Section: Introductionmentioning
confidence: 99%
“…In these patients, dose adjustment is often overlooked for drugs that are predominantly cleared by metabolism and/or transport. However, non-renal clearance of compounds requiring hepatic metabolic clearance is also known to be reduced in ESRD patients [1,2]. …”
Section: Introductionmentioning
confidence: 99%
“…The biliary clearance of digoxin has been directly measured in patients with atrial fibrillation and reported to be diminished by an average 42% secondary to quinidine (Angelin et al 1987). These extrarenal mechanisms may explain the quinidine-induced elevation of serum digoxin concentration seen in patients with renal failure Fenster et al 1982b;George & Renwick 1982;Hirschberg et al 1981).…”
Section: + +mentioning
confidence: 99%
“…In these patients, dose adjustment is rendered unnecessary for drugs that are exclusively cleared by hepatic metabolism. However, nonrenal clearance involving metabolic clearance is known to be reduced in ESRD patients . For example, the concentration of propranolol, which is the substrate of cytochrome P450 (CYP) 1A2 and CYP2D6, has been reported to be higher in ESRD patients .…”
mentioning
confidence: 99%